Dinamika Investasi Tiongkok di Sektor PLTU Batu Bara Indonesia Periode 2012-2022 - Vianeyssa, Stella Maris; Setiawan, M. Chairil Akbar (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2024)
This research aims to examine the dynamics of Chinese investment in the Indonesian coal-fired power plant sector during the period 2012-2022. The selection of this timeframe was made to illustrate the differences in Chinese investment policies in the Indonesian coal-fired power plant sector before and after the establishment of the Chinese BRI, as well as the shift in President Xi Jinping's policies from being proactive in investing to wanting to halt investments in this sector. This study utilizes the FDI Theory and Market Deregulation Theory. It employs a descriptive qualitative approach with two sources of data: primary and secondary data through interviews with WALHI and the Ministry of Investment/Indonesia Investment Coordinating Board, official government websites, specific institutional journals, previous literature, books, journal publications, and relevant news articles. The study argues that Chinese investment in the Indonesian coal-fired power plant sector, especially during the period 2012-2022, tends to have negative impacts and leads to a domino effect on economic, social, and environmental dynamics. The destructive nature of coal-fired power plant activities has led to the cessation of Chinese funding in this sector. Consequently, the Indonesian government has been encouraging Chinese and other investors to shift towards investing in renewable energy sources to replace the obsolete use of coal-fired power plants. The ultimate outcome of the research suggests the possibility of a complete transition from the Indonesian coal-fired power plant sector in the future within an undetermined timeframe.